Statuary and Classicism in Harrison's The Loiners and Beyond. Issue 1 (2nd January 2018) - Hall, Edith
ABSTRACT: A recurring element of the landscape of Tony Harrison's poetry is the sculpted image, especially the classical artistic figure, which still haunts the modern world's visual field – the realistic human form metamorphosed into metal, stone or timber. This essay identifies some of the aesthetic and political functions which they fulfil in a selection of his works, starting from his documented fascination with Nietzsche's statement that tragic poetry, like the tragic mask, or Perseus' mirror, allows humans to look at intolerable suffering entailed by the human predicament without being turned into stone. The last part of the essay stresses Harrison's portrayal of the processes of flux, change and metamorphosis of matter, processes which produce or are symbolised by anthropomorphic artefacts (above all the moment when the miners are melted down in the furnace to produce the statue of Prometheus) and argues that these crucial moments in his works are an expression both of his fascination with the visual as well as the literary forms inherited from classical antiquity, and of his fundamentally materialist philosophical outlook.